1997
DOI: 10.1177/0022022197286006
|View full text |Cite
|
Sign up to set email alerts
|

Context-Specific Measurement of Individualism-Collectivism on the Individual Level

Abstract: Cross-cultural research would be greatly aided by the availability of psychometrically sound measures of meaningful cultural dimensions of variability on the individual level. We report six studies that establish the validity and reliability of an individual-based assessment inventory of individualistic versus collectivistic tendencies in four social relationships (the Individualism-Collectivism Interpersonal Assessment Inventory-ICIAI). The results of the first five studies provide strong evidence for the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
2
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 11 publications
6
99
2
3
Order By: Relevance
“…Secondly, in line with several other researchers (e.g. Matsumoto, Weissman, Preston, Brown, & Kupperbusch, 1997;Rhee, Uleman, & Lee, 1996), we believe that there is a need for scales that measure individualism and collectivism as two separate dimensions and that do so with respect to specific contexts or types of social relationship. Therefore, in the second part of the article we examine whether individualism generalizes across various domains of social relations.…”
Section: Purpose Of the Studysupporting
confidence: 75%
See 1 more Smart Citation
“…Secondly, in line with several other researchers (e.g. Matsumoto, Weissman, Preston, Brown, & Kupperbusch, 1997;Rhee, Uleman, & Lee, 1996), we believe that there is a need for scales that measure individualism and collectivism as two separate dimensions and that do so with respect to specific contexts or types of social relationship. Therefore, in the second part of the article we examine whether individualism generalizes across various domains of social relations.…”
Section: Purpose Of the Studysupporting
confidence: 75%
“…The Individualism-Collectivism Assessment Inventory (ICAI) of Matsumoto and his associates (Matsumoto, Kudoh, & Takeuchi, 1996;Matsumoto, Weissman, Preston, Brown, & Kupperbusch, 1997) examined individualism and collectivism within the four reference groups, family, friends, colleagues, and strangers. Their study showed that common notions of individualism and collectivism between various cultures and ethnicities were indeed carried by specific social relationships.…”
Section: Target/context-specific Nature Of Individualism and Collectimentioning
confidence: 99%
“…Therefore, to determine the behavioral consequences of allocentricism, situation cues in the form of perceived relationships with the target audience have to be introduced (Kashima & Hardie, 2000). It is also suggested that scenarios-context specific cues-are more appropriate for assessing the self-related psychological processes (see Matsumoto, Weissman, Preston, Brown, & Kupperbusch, 1997;Triandis, Chen, & Chan, 1998) in Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…All participants completed an abbreviated, 20-item version of the SDS and an abbreviated, 19-item version of the ICIAI (values only), which has been used reliably and validly in Japan (Matsumoto et al, 1997). The items on the SDS were those that had the highest item-total correlations on both subscales in Study 1 (asterisked items in the appendix).…”
Section: Methodsmentioning
confidence: 99%